2015
DOI: 10.1097/txd.0000000000000528
|View full text |Cite
|
Sign up to set email alerts
|

Clostripain, the Missing Link in the Enzyme Blend for Efficient Human Islet Isolation

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 45 publications
(40 reference statements)
1
23
0
Order By: Relevance
“…As the patients usually require a repeated islet infusion, and not all islet isolations lead to clinical transplantation, the real cost for islet transplantation is higher. The islet isolation process does therefore represent a significant potential for cost reduction, and investigations into increasing the success rate and developing more efficient, low‐cost isolation techniques are ongoing . It is also important to note that isolations that fail to yield transplantation level amount of islets often result in human islets available to research .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the patients usually require a repeated islet infusion, and not all islet isolations lead to clinical transplantation, the real cost for islet transplantation is higher. The islet isolation process does therefore represent a significant potential for cost reduction, and investigations into increasing the success rate and developing more efficient, low‐cost isolation techniques are ongoing . It is also important to note that isolations that fail to yield transplantation level amount of islets often result in human islets available to research .…”
Section: Discussionmentioning
confidence: 99%
“…The islet isolation process does therefore represent a significant potential for cost reduction, and investigations into increasing the success rate and developing more efficient, low-cost isolation techniques are ongoing. 25,26 It is also important to note that isolations that fail to yield transplantation level amount of islets often result in human islets available to research. 27,28 This is a favorable part of an islet program that should not be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent study has shown that supplementation of CIzyme Collagenase, Thermolysin with Clostripain improved human islet isolation outcomes. 45 The new Liberase MTF C/T is a highly purified GMP-grade and animal tissue free product with lower endotoxin levels. Therefore, lot-to-lot variability has been minimum providing very stable enzyme mixtures.…”
Section: Discussionmentioning
confidence: 99%
“…Although the NB-1 Collagenase and NB Protease continues to be used by many laboratories, one group found that those lots with higher amounts of clostripain activity gave higher human islet yields [49]. Another group found the addition of clostripain to Collagenase HA/thermolysin enzyme mixtures increased islet yields [50]. The relevance of adding clostripain to purified collagenase-protease enzyme mixtures will be discussed in more detail below.…”
Section: ++++mentioning
confidence: 99%
“…Many laboratories are unaware of this change and continue to assume that thermolysin in the MTF kit is at a similar concentration as Liberase HI (version 4). Others addressed the problem by reducing the amount of thermolysin used in the isolation procedure [6,50].…”
Section: Selection and Dose Of Neutral Protease Is Critical For Succementioning
confidence: 99%